Quelques aspects sociologiques de la Franc-maçonnerie - Groenman, S. (Social compass, 1963)
The sociological analysis of Freemasonry is rendered difficult by the fact that it is impossible to estimate exactly its social significance and its influence, since it has no definite ideology. The author indicates, nevertheless, the conditions and lines on which a com bined study could be made.